Values-based leadership: Culture vs. Strategy - Kimberly Miloch; Abigail Tilton; Chris Ray (Academic Chairpersons Conference Proceedings, 2020)
Using Google’s Project Aristotle re:Work framework (2012), psychological safety principles (Edmondson, 1999; Edmondson & Lei, 2014), and Sinek’s (2009) purposeful leadership tenets, this workshop will engage participants in refining a leadership philosophy; in outlining steps to create a values-based culture; and in creating high performing research teams and committees.
Keywords: Values; Culture; Psychological Safety; Leadership; Teams